Living Qur'an Approach to Improve Critical Thinking Skills in Islamic Religious Education Learning - Maisyanah; Rahman, Arif; Kholis, Nur; Bakar, M. Yunus Abu; Hasan, Ali Akbar Al (LETIGES, 2024)
This study explores applying the Living Qur'an approach in Islamic education to develop critical thinking skills and a reflective and relevant understanding of Islamic teachings in students' lives. This study uses the Systematic Literature Review (SLR) method to collect evidence of applying the Living Qur'an in Islamic education. Relevant literature was selected from the Garuda, Google Scholar, and Scopus databases. Articles that met the inclusion criteria were evaluated and analysed based on the themes of experiential learning and improving critical thinking skills. The findings were analysed to understand the impact of the Living Qur'an in developing Islamic learning. The results of the study show that the Living Qur'an approach bridges the gap between the text of the Qur'an and students' social lives, making it more relevant and applicable. This approach integrates Islamic teachings with social, cultural, and gender contexts, such as in the division of inheritance in South Kalimantan and Mandar culture. The Living Qur'an encourages critical and reflective thinking, inviting students to apply Islamic teachings daily. The innovation of digital interpretation allows learning to be more interactive and to the needs of the times. In addition, the Living Qur'an plays a role in shaping social ethics, improving the quality of community life, and strengthening students' character through applicable religious education. Implementing the Living Qur'an in Islamic Religious Education learning includes contextual, value-based, interactive, collaborative, and project-based approaches. Methods such as Discovery Learning, discussion, and Problem Based Learning are used to apply the values of the Qur'an. The limitations of this study lie in the focus on limited literature and the SLR methodology that does not include direct empirical data from students. Further research is recommended to involve field studies to test the practical application of the Living Qur'an in a broader educational context, including its influence on student learning outcomes.